Pelatihan GPS untuk Pembuatan Peta Menggunakan Software QGIS Bagi SMK Penerbangan Technoterapan - Suriyanto Bakri; Alam Budiman Thamsi; Sitti Ratmi Nurhawaisyah; Muhammad Idris Juradi (Universitas Pahlawan Tuanku Tambusai, 2022)
Advances in technology for making maps based on satellite imagery make it very easy for users, including in the fields of geology and mining. As a cadet majoring in Mining geology at the Applied Techno Aviation Vocational School in Makassar, you should know and be able to use GPS and be able to process the data into a map using QGIS software, but on the other hand, there are no GPS tools and software in schools. Therefore, the UMI Community Service Institute (LPkM) through its novice service provider held a GPS Training for Making Maps Using QGIS Software. The method applied is to provide materials and training in a blended system, then monitoring and evaluation are carried out. The cadets can understand and use GPS, understand the basic concepts of maps, and can create maps using QGIS software after attending the training. The value of Sig.(2-tailed) was 0.0000.04, proving that there was a difference between before and after the training, so it can be concluded that the training had a positive impact on increasing the cadets' understanding regarding the use of GPS and QGIS.